Resilience, and Agile Closed-Loop Supply Chain Network Design by Considering Renewable Energy - Gholamian, Seyyed Akbar (International journal of industrial engineering and operational research, 2024)
This paper explores the integration of resilience, agility, and closed-loop practices within supply chain network design (SCND) while incorporating renewable energy sources. A novel Resilience, and Agile Closed-Loop Supply Chain Network (RACLSCND) concept is introduced, aiming to achieve sustainability and robustness in a circular economy. The literature review examines existing research on resilient SCND, closed-loop supply chains, and the role of renewable energy in these systems. The methodology proposes a Robust Stochastic Optimization (RSO) model that considers factors like renewable energy integration, facility location, capacity planning, and material flow optimization. Numerical results demonstrate the effectiveness of the model in a case study from the home appliance industry. The model optimizes network design while minimizing carbon footprint and ensuring adaptability to demand fluctuations. The conclusion emphasizes the significance of RACLSCND as a future-proof approach for sustainable and resilient supply chain management.